PENGARUH DISIPLIN KERJA DAN MOTIVASI TERHADAP KINERJA KARYAWAN MJ PRODUCT: The Effect of Work Discipline and Motivation on Employee Performance at MJ Product - Devy Naila; Hotner Tampubolon; Jonny Siagian (Universitas Kristen Indonesia, 2026)
These researched aim to analyze influence of work disciplines and motivation on the performances of MJ Product employee. The research methods use is quantitative, descriptive in nature. Data was collected through questionnaires distributed to 30 employees. Analysis was carried out using primarlly data which was collected through observations, interview and distributing questionnaires. Analyst was carried out use the Statistically Products and Services Solution (SPSS) software tool versions 25. The data analyst techniques in this research use multiple linear regressions. The research result show that work disciplines and motivations have a positive and significancy influence on employee performances, both partially and simultaneously. Base on result of the hypothesis of the simultaneous influence of work disciplines and motivations on employee performances, a coefficients of determination value of 87.5% was obtained. It may be conclude that work discipline and motivation influence employee performance at MJ Product. So it may be conclud that work disciplines and motivations influence employee performances at MJ Product. Keywords: Work Discipline, Motivation, Employee Performance